2019
DOI: 10.1038/s41380-019-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of dopamine and serotonin on resting-state networks: review and implications for psychiatric disorders

Abstract: Alterations in brain intrinsic activity-as organized in resting-state networks (RSNs) such as sensorimotor network (SMN), salience network (SN), and default-mode network (DMN)-and in neurotransmitters signaling-such as dopamine (DA) and serotonin (5-HT)-have been independently detected in psychiatric disorders like bipolar disorder and schizophrenia. Thus, the aim of this work was to investigate the relationship between such neurotransmitters and RSNs in healthy, by reviewing the relevant work on this topic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 116 publications
6
134
1
1
Order By: Relevance
“…Maternal cannabis use likely affects fetal development of numerous circuits, but effects on the mesocorticolimbic system may have particularly strong impacts on future psychiatric health of the offspring. The functioning of this system is regulated by dopamine, a neurotransmitter highly implicated in various psychiatric and substance use disorders, and its receptors are involved in developmental differentiation and circuit formation of the forebrain (Frederick and Stanwood, 2009;Conio et al, 2019). Human fetal studies have documented alterations in dopamine D2 receptor (DRD2) gene expression in mesocorticolimbic brain structures after in utero cannabis exposure (Wang et al, 2004(Wang et al, , 2006.…”
Section: Maternal Thc Biases Offspring Dopamine System Toward Behaviomentioning
confidence: 99%
“…Maternal cannabis use likely affects fetal development of numerous circuits, but effects on the mesocorticolimbic system may have particularly strong impacts on future psychiatric health of the offspring. The functioning of this system is regulated by dopamine, a neurotransmitter highly implicated in various psychiatric and substance use disorders, and its receptors are involved in developmental differentiation and circuit formation of the forebrain (Frederick and Stanwood, 2009;Conio et al, 2019). Human fetal studies have documented alterations in dopamine D2 receptor (DRD2) gene expression in mesocorticolimbic brain structures after in utero cannabis exposure (Wang et al, 2004(Wang et al, , 2006.…”
Section: Maternal Thc Biases Offspring Dopamine System Toward Behaviomentioning
confidence: 99%
“…Gut-Brain Axis: Probiotic, Bacillus subtilis, Prevents Aggression via the Modification… DOI: http://dx.doi.org/10.5772/intechopen.86775 [91][92][93][94] and social behavior [95,96], affecting mental health [97][98][99][100] and providing therapeutic strategy for treating or preventing stress reaction and related neuropsychiatric disorders [94,97].…”
Section: Gut Microbiota and The Gut-brain Axismentioning
confidence: 99%
“…Previous studies have rarely reported the direct impact of COMT polymorphisms on resting-state FFA activity in healthy people. Some studies focusing on the interaction effect between the COMT rs4680 and other dopamine-function related generic variants imply that dopamine-related neurons may affect the baseline brain resting state activity by synchronizing the low-frequency oscillation 50 . Moreover, dopamine could stabilize (keep the balance between facilitating and suppressing) neural signaling in brain networks responsible for behavior-stimuli oriented attention 51,52 .…”
Section: Discussionmentioning
confidence: 99%